A new analytical method to the conformable chiral nonlinear Schrodinger equation in the quantum Hall effect - Yel, Gulnur; Bulut, Hasan; Ilhan, Esin (Indian Acad Sciences, 2022)
In this work, our goal is to find more general exact travelling wave solutions of the (1+1)- and (2+1)-dimensional nonlinear chiral Schrodinger equation with conformable derivative by using a newly developed analytical method. The governing model has a very important role in quantum mechanics, especially in the field of quantum Hall effect where chiral excitations are present. In two-dimensional electron systems, subjected to strong magnetic fields and low temperatures, the quantum Hall effect can be observed. By using the method, called the rational sine-Gordon expansion method which is a generalised form of the sine-Gordon expansion method, we found complex dark and bright solitary wave solutions. These solutions have important applications in the quantum Hall effect.
Keywords: Rational sine-Gordon expansion method; conformable derivative; chiral nonlinear Schrodinger equation; quantum Hall effect